Nilai sosial dalam Novel Tenggelamnya Kapal van Der Wijck karya Hamka - Saifullah, Saifullah (Cakrawala Indonesia, 2023)
Social Values ​​in Hamka's Novel Sinking of the Van Der Wijck Ship.The problem in this research is the study of space and time, character, and social situation in Hamka's novel Tenggelamnya Kapal van der Wijck. The method used is descriptive method with a qualitative research form. The source of the data in this study was Hamka's novel The Sinking of the Van Der Wijck Ship. The techniques used are literary techniques and note-taking techniques. Based on the results of research on the novel related to sociological aspects, it was found: 1) Space and time in the novel describe the condition of a society that is very dependent on customs and traditions. Apart from that, the condition of the Indonesian nation as a whole was under Dutch control, causing conditions in several regions to be heavily influenced by the association of Dutch people. 2) The character shown depicts a figure who so glorifies customs and traditions. In addition, it also describes life that is influenced by the habits of western people who are free and modern. 3) The social situation in the novel describes the life of the people who are united in the bonds of customs and traditions, besides that it also describes the society which is influenced by the free life of western people. Keywords:Social Value, The Sinking of the Van Der Wijck Ship